Between Baghdad and Khurasan: Early Sufism in Islamic History at 7-9 M Century - Mahendra, Fahmi Rizal; Aldiansyah, Muhammad; Wulandari, Rifdah Shofiyyah; Prakasa, Mursyidan; Faradis, Shilna (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
This article describes the early movements of Sufism or Sufism in Islamic history. By using the historical method, this article explains the origins of Sufism, both from the teachings, sources, first figures and early developments in the history of early Sufism. The focus of this article is the early development of Sufism in two different areas, namely Baghdad and Khurasan. Each region gave birth to different figures, styles of thought and teachings of early Sufism. In general, the Baghdad school is famous for its "conscious" teachings, which are different from the Khurasan school, which is known for being "drunk" or "unconscious". Historically Sufism was born as an individual movement that was born to respond to the complex political situation of Muslims after the death of the Prophet Muhammad. Initially this movement was individual before eventually developing into a group movement or forming schools with different styles of teachings